DEPOLIMERISASI KITOSAN DENGAN HIDROLISA ENZIMATIK MENGGUNAKAN ENZIM α-AMILASE - Hanik Handayani P.L.; Paramarta Siwi R.; Nur Rokhati (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Chitosan is a polymer derivative of chitin that has many benefits in food and medical. Since chitosan has a large molecular weight, it has constraints to its application. To overcome the disadvantage, it needs hydrolysis of chitosan in order to obtained a lower molecular weight. In this research the hydrolysis of chitosan will  be operated by enzymatic process uses thermophilic enzyme α-amylase. The experiment begins by making a chitosan solution 1% w/v in an acetic acid solution 1% v/v. The chitosan solution is hydrolyzed using the enzyme α-amylase with varied pH, operating temperature, time, and ratio of the enzyme:substrate to obtain the optimum. The response comprehends Dextrose Equivalent (DE), viscosity, and the average of molecular weight. The results showed that the optimum operating conditions for chitosan hydrolysis using α-amylase enzyme is at pH 5, temperature 90 °C, 2 hours operating time, and ratio of enzyme:substrate 1:2500 (0,1 ml). For variable pH, temperature, time, and enzyme addition, DE rises meanwhile variables are increased, then it dropped significantly after the optimum level. The hydrolysis can reduce molecular weight of chitosan from 1680-1750 kDa to 144,18 kDa thus it is included to MMWCs.